Memanfaatkan Potensi Lokal Kefamenanu dalam Pembelajaran Matematika Untuk Meningkatkan Kreativitas Guru SMP - Stanislaus Amsikan; Yohanis Ndapa Deda (LPPM Universitas Timor, 2018)
The purpose of this study is to creative teachers in making worksheets students (LKS) using local potential in Kefamenanu, North Central Timor Regency (TTU). Local potential that we meanin this research is local traditional food laku tobe, guava local in timor region, traditional house ume kbubu, and sotis woven traditional motives . The methods used is discourse, workshop, and practice. This method used to convey an overall picture and example using local potential in learning math, then followed by analysis of main competence and basic competence in wich coresponding to the potential local, the final phase is practice, where teachers as participants workshop follow in the classroom using LKS based potential local.The result shows that laku tobe local potential, guava , ume kbubu , and motif woven in kefamenanu has been proven creative teachers.